2017
DOI: 10.4103/ijpvm.ijpvm_258_17
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin induces apoptosis in human bladder cancer cell lines through reactive oxygen species, mitochondrial membrane potential, and cytochrome C pathway

Abstract: Background:Dihydroartemisinin (DHA) is a semisynthetic derivative of artemisinin and has antiproliferative effect. However, such effects of DHA have not yet been revealed for bladder cancer cells.Methods:We used as bladder cancer cell lines to examine the effect of DHA on the cell viability, cell apoptosis, and monitoring of mitochondrial membrane potential (ΔΨm) changes. Furthermore, the effect of DHA on the reactive oxygen species (ROS) production and cytochrome c release were also detected. We employed MTT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…The maintenance of the mitochondrial membrane potential (Δψm) is crucial for mitochondrial function. The collapse of ΔΨm and depletion of ATP are the direct consequences of ROS accumulation in mitochondria, and these events precede the release of cytochrome c and activation of the caspase protease cascade [ 38 ]. We have found that AGEs induce a significant depletion in the ΔΨm of GMCs, a result that is in agreement with those reported in previous studies [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of the mitochondrial membrane potential (Δψm) is crucial for mitochondrial function. The collapse of ΔΨm and depletion of ATP are the direct consequences of ROS accumulation in mitochondria, and these events precede the release of cytochrome c and activation of the caspase protease cascade [ 38 ]. We have found that AGEs induce a significant depletion in the ΔΨm of GMCs, a result that is in agreement with those reported in previous studies [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…6B ). The decrease of MMP has been associated with the increase of ROS, and with cell apoptosis ( 11 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Bax and Bcl2 protein were determined by immunoblotting assays as described previously(2122). The cells were treated with different concentrations of Gal-9 (1, 50, and 100 nM) for 48 h. Prepared lysates at 30-50 μg amounts were subjected to SDS-PAGE and transferred onto polyvinylidene difluoride (PVDF) membrane.…”
Section: Methodsmentioning
confidence: 99%